2015
DOI: 10.1371/journal.pone.0137871
|View full text |Cite
|
Sign up to set email alerts
|

A New Sandwich ELISA for Quantification of Thymidine Kinase 1 Protein Levels in Sera from Dogs with Different Malignancies Can Aid in Disease Management

Abstract: Thymidine kinase 1 (TK1) is a DNA precursor enzyme whose expression is closely correlated with cell proliferation and cell turnover. Sensitive serum TK1 activity assays have been used for monitoring and prognosis of hematological malignancies in both humans and dogs. Here we describe the development of a specific sandwich TK1-ELISA for the quantification of TK1 protein levels in sera from dogs with different malignancies. A combination of rabbit polyclonal anti-dog TK1 antibody and a mouse monoclonal anti-huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…These results are in concordance with previous studies suggesting that in treated dogs with increased sTK1 activity at diagnosis, sTK1 activity drops to minimal level when the clinical remission has been achieved. 49,[53][54][55]73 One limitation in this study is that dogs were not completely restaged at the time of their best clinical response and sTK1 activity measurement to confirm the CR status. In 9 of 36 (25%) dogs classified as being in complete remission, the sTK1 activity remained above 20 Du/L at the time of their best response.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in concordance with previous studies suggesting that in treated dogs with increased sTK1 activity at diagnosis, sTK1 activity drops to minimal level when the clinical remission has been achieved. 49,[53][54][55]73 One limitation in this study is that dogs were not completely restaged at the time of their best clinical response and sTK1 activity measurement to confirm the CR status. In 9 of 36 (25%) dogs classified as being in complete remission, the sTK1 activity remained above 20 Du/L at the time of their best response.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent report confirmed that the early results could be recapitulated in a different population using a non-radiometric immunoassay with high correlation ( 16 ). This assay has shown promise as a biomarker of disease, prognosis, and monitoring ( 13 , 17 19 ). The commercial application of this assay will be discussed subsequently.…”
Section: Cellular Leakage Enzymesmentioning
confidence: 99%
“…It is also known that TK1 can form different complexes. Some of these complexes in serum having abnormal molecular weights of up to 240 kDa and 730 kDa [30][31][32][33]. Therefore, antibodies targeting only one region of the TK1 protein may limit the detection of TK1 to specific forms of the enzyme.…”
mentioning
confidence: 99%